THE LEAST SQUARES METHOD AS A TOOL FOR SHORT-TERM FORECASTING OF EPIDEMIOLOGICAL DYNAMICS - Zhumartova Б.; Utemisova А.; Ysmagul Р.С. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
Humanity at all times closely interacts with various viruses, bacteria, fungi, some of them we owe our lives, some are dangerous for us, they are sources of infection. In the second decade of the 21st century, the world faced an invisible "enemy" coronavirus infection, which required rapid, decisive action from the world community not only in the fight against it, but also in the search for methods and ways to predict its spread. In order to calculate the maximum burden on the healthcare sector and adjust infection containment measures, mathematical modeling is necessary. Like any phenomenon in our life, the spread of infectious diseases can be modeled using mathematical apparatus. Which, in turn, will make it possible to predict the rate of infection, to anticipate the future scenario of infection of the population. To this end, the article considered the least squares method (OLS) for predicting the epiddynamics of coronavirus infection in the territory of Kostanay region.